Beyond Entertainment: TikTok's Influence on EFL Vocabulary Development - Muhammad Safwanulhadi; Safrul Muluk (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
This study examines how TikTok affects English as a Foreign Language (EFL) students' vocabulary acquisition at UIN Ar-Raniry Banda Aceh. The research was prompted by the growing use of social media in everyday life and the potential of digital platforms to help students learn vocabulary in informal settings. Prior research has shown that social media can help with language learning. However, there aren't many studies that focus on students' experiences in Aceh and how TikTok helps them learn vocabulary outside of school. This research used a qualitative descriptive approach. Fourteen students from the English Education Department's 2022 cohort were selected through purposive sampling based on their active use of TikTok and engagement with English-language content on the platform. Data collection involved an open-ended questionnaire, and thematic analysis was used for data analysis. The research indicates that TikTok impacts vocabulary development through four primary mechanisms. Vocabulary acquisition often occurs incidentally, driven by repeated exposure to entertaining and subject-specific content. Moreover, TikTok promotes learning by using different types of input, such as sound, text, and images. At the same time, the platform's algorithms help people remember things better. Third, the platform creates an engaging and accessible learning environment because its short videos are practical, appealing, and easy to access. Fourth, its effectiveness remains conditional, as distractions, limited depth, random content exposure, and a lack of active practice may reduce learning outcomes.